BS EN 2821. Aerospace series. Steel X5CrNiCu15 5 (1.4545). Consumable electrode remelted. Solution treated and precipitation treated. Bars for machining. a or D ≤ 200mm. Rm ≥ 1 310 MPa. (21st July 2021) - British Standards Institution
No abstract available